Fenbendazole induces pyroptosis in breast cancer cells through HK2/caspase-3/GSDME signaling pathway - Pan, Tingting; Jin, Shengqi; Huang, Xiaoxia; Xin, Xin; Xing, Qiming; Yang, Wenhui; Dong, Jing; Li, Lin (Frontiers in Pharmacology, 2025)
IntroductionPyroptosis, a gasdermin (GSDM) - mediated programmed cell death associated with inflammation, has emerged as a promising strategy for cancer therapy. Metabolic reprogramming, a hallmark of cancer, presents potential targets for malignancy intervention. Fenbendazole (FBZ), a safe and inexpensive antiparasitic drug, has shown antitumor activities, but its underlying mechanisms remain unclear.MethodsWe investigated the effects of FBZ on mouse mammary carcinoma cells in vitro using CCK - 8 assays, qPCR, Western blotting, and LDH release assays. Pyroptotic morphology was observed by microscopy. In vivo, we evaluated the antitumor efficacy of FBZ in a mouse mammary carcinoma model, analyzing tumor volume, weight, and histopathology. The involvement of the caspase - GSDM pathway and glycolysis (via hexokinase 2, HK2) was explored.ResultsIn vitro, FBZ dose - dependently inhibited cell viability, induced pyroptotic morphological changes (e.g., cell swelling and membrane pore formation), upregulated pyroptosis markers (cleaved caspase - 3, GSDME - NT, IL - 1β), and suppressed glycolysis by downregulating HK2. In vivo, FBZ treatment significantly reduced tumor volume and weight, with minimal systemic toxicity. Mechanistically, FBZ activated the caspase - 3/GSDME pathway and inhibited HK2 - dependent glycolysis.ConclusionOur findings reveal that FBZ suppresses tumor growth by inducing pyroptosis and inhibiting glycolysis via HK2 downregulation. This study uncovers a novel mechanism for FBZ’s antitumor effects and highlights HK2 as a critical link between metabolism and cell death, suggesting FBZ as a potential candidate for cancer therapy.